Answer:
v-u = (-7,5)
Explanation:
Given
u has an initial point of (2,-1 ) and a terminal point of (3, 1)
And
v = (-6,7)
First of all we have to find the vector u. for this purpose the initial point is subtracted from the termination point.
Let
![P_1 = (2,-1)\\P_2 = (3,1)\\then\\u = P_2-P_1\\= (3,1) - (2,-1)\\= (3-2, 1+1)\\=(1,2)](https://img.qammunity.org/2021/formulas/mathematics/college/rp7srs7e4cxhybubpygazjpgc1175jb60o.png)
The vector u is (1,2)
Now we have to find v-u
So,
![v-u = (-6,7) - (1,2)\\= (-6-1,7-2)\\=(-7,5)](https://img.qammunity.org/2021/formulas/mathematics/college/aifw7w9p2r89f5p9gvb70vvbyrmdp9x1l7.png)
Hence,
v-u = (-7,5)